The causal effects of inflammatory and autoimmune skin diseases on thyroid diseases: evidence from Mendelian randomization study - You, Ruixuan; Duan, Jiayue; Zhou, Yong; Yu, Jiangfan; Zou, Puyu; Wei, Yi; Chai, Ke; Zeng, Zhuotong; Xiao, Yangfan; Yuan, Lingqing; Xiao, Rong (Frontiers in Endocrinology, 2024)
To clarify the controversy between inflammatory or autoimmune skin diseases and thyroid diseases, we performed two-sample Mendelian randomization (MR) analyses.Genetic data on factors associated with atopic dermatitis (AD, n=40,835), seborrheic dermatitis (SD, n=339,277), acne (n=363,927), rosacea (n=299,421), urticaria (n=374,758), psoriasis (n=373,338), psoriasis vulgaris (n=369,830), systemic lupus erythematosus (SLE, n=14,267), vitiligo (n=353,348), alopecia areata (AA, n=361,822), pemphigus (n=375,929), bullous pemphigoid (BP, n=376,274), systemic sclerosis (SSc, n=376,864), localized scleroderma (LS, n=353,449), hypothyroidism (n=314,995 or n=337,159), and hyperthyroidism (n=281,683 or n=337,159) were derived from genome-wide association summary statistics of European ancestry.The inverse variance weighted method was employed to obtain the causal estimates of inflammatory or autoimmune skin diseases on the risk of thyroid diseases, complemented by MR-Egger, weighted median, and MR-pleiotropy residual sum and outlier (MR-PRESSO).AD, SLE, SD, and psoriasis vulgaris were associated with an increased risk of hypothyroidism, whereas BP was associated with a lower risk of hypothyroidism (all with p < 0.05). The multivariable MR analyses showed that AD (OR = 1.053; 95%CI: 1.015-1.092; p = 0.006), SLE (OR = 1.093; 95%CI: 1.059-1.127; p < 0.001), and SD (OR = 1.006; 95%CI: 1.002-1.010; p = 0.006) independently and predominately contributed to the genetic causal effect on hypothyroidism after adjusting for smoking. The results showed no causal effects of inflammatory or autoimmune skin diseases on hyperthyroidism.The findings showed a causal effect of AD, SLE, SD on hypothyroidism, but further investigations should be conducted to explore the pathogenic mechanisms underlying these relationships.